Apical plug with bioceramic cement in the treatment off teeth with incomplete root formation: Case report (Research, Society and Development, 2024)
The aim of this article is to report a clinical case in which the apexification technique with bioceramic cement was used to make an apical plug in a tooth with incomplete rhizogenesis. Endodontic treatment was carried out on a patient who arrived at the dental clinic of the State University of Maringá and was diagnosed with pulp necrosis and a periapical lesion on tooth 21. The materials and methods used to treat this case consisted of manufacturing an apical plug using Sealer Plus BC bioceramic cement (MK Life). The results presented showed the effectiveness of bioceramic materials in dentistry for the management of perforations, root resorption, open apex canals, among other cases, due to the ability of these substances to induce biomineralization.